Evaluation of different OCT systems in quantitative imaging of human Schlemm's canal - Wu, Xuan (2022)
We examined the performance of human Schlemm's canal (SC) imaging using different OCT devices: CIRRUS 5000 (840 nm, spectral-domain (SD)-OCT), PLEX Elite 9000 (1060 nm, swept-source (SS)-OCT) and CASIA SS-1000 (1310 nm, SS-OCT), and analyzed potential impact factors on visualization and the quantitative assessment of SC morphology in a pilot study. Ten healthy subjects were imaged using three OCT devices by a single experienced operator on the same day. Each eye underwent two cubic scans by each device, one on nasal and the other on temporal quadrant. The B-scan showing the largest SC was manually selected for processing. Four quantitative metrics, including one morphological metric as cross-sectional area (CSA), and three performance metrics as contrast, continuity, and coverage, were derived from the datasets. Repeated-measures ANOVA was used to investigate the difference between these parameters from the three devices (P < 0.05). We found the CSA measured from CIRRUS was significantly larger than PLEX, followed by CASIA. The contrast was highest in CIRRUS, followed by PLEX and CASIA. The coverage was also higher in CIRRUS as compared to PLEX and CASIA. No significant difference was seen in the continuity from the three devices. In summary, we showed the measurements from the three devices were not interchangeable.